Worlds apart or two sides of the same coin? Attitudes, meanings, and motives of potential oocyte and sperm donors in Austria - Flatscher-Thöni, M. (J Assist Reprod Genet, 2020)
PURPOSE: Gamete donors and recipients of such donations have been explored by previous studies, which mostly focus on post-donation scenarios. Our study analyses the general willingness to donate oocytes or sperm and focuses on differences between potential female and male donors in attitudes, meanings, and motives in a pre-donation setting. METHODS: An electronic survey (n = 555 students) was used in this anonymous observational study. To enable comparisons between men and women regarding their attitudes, meanings, and motives and their willingness to donate gametes, we designed two separate questionnaires. RESULTS: The sample was divided into three groups based on the willingness to donate: potential donors (n = 133; women: 48.1%, men: 51.9%); doubtful donors (n = 207; women: 75.8%, men: 24.2%); and non-donors (n = 215; women: 68.3%, men: 31.7%). The group of potential male donors (39.2%) was significantly larger than the group of potential female donors (16.9%). Significant differences regarding altruism, the meaning of one’s self-worth, and passing on the own genes were found between doubtful and potential donors. Potential donors attached less value to altruism but more value to the enhancement of one’s self-worth and passing on one’s genes than doubtful donors. The motive of passing on one’s genes and altruistic motives were more important to men than to women. CONCLUSION: This study helps to create a better understanding of potential donors in the existing donation framework and supports the evaluation of the given regimes in the context of designing an improved framework.